Traditional Rulers, Families, and Waqf: Their Roles in Promoting Early Childhood Literacy and Numeracy Skills in Gombe and Adamawa States, Nigeria - Adamu Abubakar Muhammad; Fadimatu Ahmed Jika; Ibrahim Abubakar Muhammad; Shafa’at Ahmad Aliyu; Human Khan; Hamed Barjesteh; Abdul Jamal; Mansoor Ali Darazi (Journal of Early Childhood Development and Education, 2026)
Background: Early childhood literacy and numeracy are essential foundations for social cohesion, lifelong learning, and sustainable development. In Northern Nigeria, these skills are shaped not only by formal education systems but also by families, traditional leaders, and religious-based support institutions such as waqf. However, empirical evidence on the specific roles and interactions of these actors remains limited. Objective: This study examines the contributions of families, traditional leaders, and waqf institutions to early childhood literacy and numeracy development in Gombe and Adamawa States, Nigeria, and identifies key challenges affecting their effectiveness. Methods: A mixed-methods design was employed, integrating survey data, structured interviews, and documentary analysis to explore institutional, cultural, and religious influences on early childhood education. Results: The findings indicate that families are the primary source of early cognitive development and value formation. Traditional leaders act as cultural custodians and intermediaries who mobilize community support for educational initiatives. Waqf institutions provide sustained financial support for community learning centres and Qur’anic schools. Nevertheless, these contributions are constrained by poverty, weak waqf institutionalization, and declining family involvement. Conclusion: The study concludes that early childhood literacy and numeracy outcomes in Northern Nigeria can be improved through a coordinated approach that strengthens collaboration among families, traditional leaders, and waqf institutions to ensure sustainable early childhood education initiatives.